Virtual training leads to physical, cognitive and neural benefits in healthy adults - Burin, Dalila; Liu, Yingxu; Yamaya, Noriki; Kawashima, Ryuta (NeuroImage (Orlando, Fla.), 2020)
Physical activity, such as high-intensity intermittent aerobic exercise (HIE), can improve executive functions. Although performing strength or aerobic training might be problematic or not feasible for someone. An experimental situation where there is no actual movement, but the body shows physiological reactions, is during the illusion through immersive virtual reality (IVR). We aimed to demonstrate whether a virtual HIE-based intervention (vHIE) performed exclusively by the own virtual body has physical, cognitive, and neural benefits on the real body. 45 healthy young adults (cross-over design) experienced HIE training in IVR (i.e., the virtual body performed eight sets of 30 s of running followed by 30 s of slow walking, while the subject is completely still) in two random-ordered conditions (administered in two sessions one week apart): the virtual body is displayed in first-person perspective (1PP) or third-person perspective (3PP). During the vHIE, we recorded the heart rate and subjective questionnaires to confirm the effectiveness of the illusion; before and after vHIE, we measured cortical hemodynamic changes in the participants’ left dorsolateral prefrontal cortex (lDLPFC) using the fNIRS device during the Stroop task to test our main hypothesis. Preliminary, we confirmed that the illusion was effective: during the vHIE in 1PP, subjects’ heart rate increased coherently with the virtual movements, and they reported subjective feelings of ownership and agency. Primarily, subjects were faster in executing the Stroop task after the vHIE in 1PP; also, the lDLPFC activity increased coherently. Clinically, these results might be exploited to train cognition and body simultaneously. Theoretically, we proved that the sense of body ownership and agency can affect other parameters, even in the absence of actual movements.